“THE TECHNOLOGICAL TOOLS USED BY TEACHERS IN VIRTUAL MODALITY FOR THE TEACHING-LEARNING PROCESS IN ENGLISH LANGUAGE” - Villegas Oña, Jennifer Karolina (2022)
Education has been characterized in recent times by the advancement in the use of technological tools since these allow the objectives aimed in the teaching-learning process to be adequately achieved. Additionally, it was affected due to the pandemic that arose during the years 2020 / 2021. Therefore, technology has been the main component of education, for this reason this research has the objective to analyze the influence of the use of technological tools for virtual classes in the teaching-learning process of English language. For this reason, the main problem of this research was: How technological tools influence virtual education and the teaching learning process of the English language? In order to carry out the analysis within the investigation, the following research parameters have been considered: a qualitative methodology that is a descriptive method applied to analyze the main factors involved in the use of technological tools for online teaching. The data collection instrument was a semi-structured interview, which contained open-ended questions that contributed to research and was applied to six English teachers from the educational institution "Dr. Trajano Naranjo Iturralde" and “Rioblanco Alto”. Data analysis was carried out using a thematic analysis that focused on coding, transcription, and finally divided into five categories, such as: the challenges of virtual education, advantages, disadvantages and the impact of professional training of it. The results showed that online teaching is not only a challenge for teachers, but also involves students, since socioeconomic factors, teacher training, the use of these digital platforms, the advantages and disadvantages that involve the virtual modality in the educational context must be taken into account, since technical issues are the main problem in the effectiveness of online classes. The study concludes that the technological tools support the teacher in the virtual mode, since through them it is possible to interact with the student, thus generating significant knowledge. However, it is necessary to take into consideration aspects that interfere in the teaching-learning process of English regarding the use and management of technology in online classes.